Marked elevation in plasma osteoprotegerin constitutes an early and consistent feature of cerebral malaria - O’Regan, Niamh; Moxon, Chris; Gegenbauer, Kristina; O’Sullivan, Jamie M.; Chion, Alain; Smith, Owen P.; Preston, Roger J. S.; Brophy, Teresa M.; Craig, Alister G.; O’Donnell, James S. (Thrombosis and Haemostasis, 2016)
Adherence of infected erythrocytes to vascular endothelium causes acute endothelial cell (EC) activation during Plasmodium falciparum infection. Consequently, proteins stored in Weibel-Palade (WP) bodies within EC are secreted into the plasma. Osteoprotegerin (OPG) binds to VWF and consequently is stored within WP bodies. Given the critical role of EC activation in the pathogenesis of severe malaria, we investigated plasma OPG levels in children with P. falciparum malaria. At presentation, plasma OPG levels were significantly elevated in children with cerebral malaria (CM) compared to healthy controls (means 16.0 vs 0.8 ng/ml; p<0.01). Importantly, OPG levels were also significantly higher in children with CM who had a fatal outcome, compared to children with CM who survived. Finally, in children with CM, plasma OPG levels correlated with other established prognostic indices (including plasma lactate levels and peripheral parasite density). To further investigate the relationship between severe malaria and OPG, we utilised a murine model of experimental CM in which C57BL/6J mice were infected with P. berghei ANKA. Interestingly, plasma OPG levels were increased 4.6 fold within 24 hours following P. berghei inoculation. This early marked elevation in OPG levels was observed before any objective clinical signs were apparent, and preceded the development of peripheral blood parasitaemia. As the mice became increasingly unwell, plasma OPG levels progressively increased. Collectively, these data suggest that OPG constitutes a novel biomarker with prognostic significance in patients with severe malaria. In addition, further studies are required to determine whether OPG plays a role in modulating malaria pathogenesis.
Keywords: Osteoprotegerin; von Willebrand factor; cerebral malaria; Plasmodium falciparum; Plasmodium berghei